A Survey on English Vocabulary Acquisition and Learning Strategies Among Kolej Permata Insan Students - Nur Ayuni Mat Rahim; Nur Insyirah Nasrul Izani; Siti Munirah Mohd; Khairul Rafique Alhalim Cairul Nidzwan; Nurhidaya Mohamad Jan; Mohamad Faiz Zainuddin (Academic Inspired Network, 2025)
Indexed Publication (Tier 3)